2011
DOI: 10.1007/s11325-011-0552-7
|View full text |Cite
|
Sign up to set email alerts
|

The influence of obesity and obstructive sleep apnea on metabolic hormones

Abstract: The basal levels of leptin, adiponectin, and ghrelin were mostly associated with obesity. We found that sleep apnea was not a determinant factor in leptin, adiponectin, and ghrelin hormonal levels. Interestingly, nCPAP treatment diminishes leptin in obese OSA patients and adiponectin levels in obese and non-obese patients with OSAS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
56
4
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(67 citation statements)
references
References 31 publications
5
56
4
2
Order By: Relevance
“…A similar result was obtained in a previous study (5), suggesting that apoA1concenteration may not be affected by the excess oxidative stress in sleep apnea. In our study OSA was not associated with alterations in adiponectin and insulin sensitivity, consistent with a recent study showing an association between adiponectin and obesity, but not OSA (35).…”
Section: Discussionsupporting
confidence: 93%
“…A similar result was obtained in a previous study (5), suggesting that apoA1concenteration may not be affected by the excess oxidative stress in sleep apnea. In our study OSA was not associated with alterations in adiponectin and insulin sensitivity, consistent with a recent study showing an association between adiponectin and obesity, but not OSA (35).…”
Section: Discussionsupporting
confidence: 93%
“…One of them was randomized clinical trial (RCT) [19], the remaining studies were observational [20][21][22][23][24][25][26][27][28][29]. One study [27] reported results separately for obese group and non-obese group. The information of author, year of publication, nation, sample size, inclusion criteria, mean daily CPAP usage time, therapy duration and study design of each study was presented in Table 1.…”
Section: Characteristics Of the Included Studiesmentioning
confidence: 99%
“…Five articles were excluded from the sample because of following reasons: four papers due to lack of data for the necessary calculation means and SMD [16,[23][24][25], another research because of the inclusion of children [26]. At last, 10 articles, containing 2 clinical randomized controlled studies, which included 289 patients met the inclusion criteria were analyzed in meta-analysis [9][10][11][12][13][14][15][17][18][19]. The principal characteristics of these studies are outlined in Table 1.…”
Section: Results General Characteristics Of Studiesmentioning
confidence: 99%
“…Alternatively, subgroup analysis suggested that possible factors which could influence the results of CPAP therapy were not observed. [11]. As we know, many disorders, such as OSA [4], overweight [5], and insulin resistance [30], were found to be associated with decreased adiponectin levels.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation